Nematofauna da planície de maré de Coroa Grande, Baía de Sepetiba, RJ - Esteves, André Morgado (2002)
Determine the generic composition, trophic structure and community structure of marine nematodes on the Coroa Grande tidal flat, Sepetiba bay, Rio de Janeiro. Brazil (22º55'00"S e 43º05' 30''W). Monthly samples were taken during Iow tides, using a corer with 1cm², from may-98 to april-99. Samples were obtained within transect strata which represent the different levels of the intertidal zone. Samples for granulometric composition, organic matter anel chlorophyll analysis were also collected. Canonical correspondence analysis (CCA) was used to evaluate the community structure. Two different classifications were used in order to determine the trophic structure. The structure of nematode community showed a spatial-temporal. with samples of the lower tidal flat level (near to the subtidal zone) forming a separate group from samples of the upper levels. A total of 31 genera were found: Anoplostoma, Bathylainnus, Comesoma, Daptonema, Enoplolainnus, Eurystomina, Halichoanolaimus, Haliplectus, Metachromadora, Oxystomina, Oncholainnus, Paracanthonchus, Paraodontophora, Sabatieria, Steineria, Sphaerolaimus, Spirinia, Terschellingia, Theristus, Viscosia and Trissonchulus. The genera Chromadorella, Chromaspirinia, Dorylaimopsis, Euchromadora, Gomphionema, Gammanema, Linhomoeus and Paramonohystera were recorded for the first time in Brazilian sediments. The faunal composition was not very different from other similar habitats. Diversity patterns were influenced by the sedimentological characteristics of the environment, especially, the amount of fine sediments. Diversity values found on the studied arca were similar to those of different studies in tropical areas; nevertheless are low when compared to temperate areas. The general patterns of lhe trophic structure were associated with the change in the abundance of the three main genera: Comesoma, Daptonema e Oncholaimus. In spatial terms, deposit feeders stricto sensu predominated in the lower level of the tidal flat, while facultative predators dominated the upper levels.